ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN PEMBIAYAAN MUDHARABAH PADA BMT HIDAYAH UMAT YOGYAKARTA 2013 - Murningsih .; Ahmad Yunadi (JESI (Jurnal Ekonomi Syariah Indonesia), 2013)
Abstract Murningsih. 2009. "Analysis of Factors Affect the Demand of Financing Mudharabah at BMT Hidayah Umat Yogyakarta in 2013”. A Thesis. Yogyakarta: School of Theology Alma Ata. KJKS BMT is an institution that serves as a financial intermediary institution. KJKS BMT distributes third party funds to the people. Among of them are mudharabah and musyarakah financing. The background of this research is that sharia, service, product, and promotion are the factors to be considered by the people to apply for funding to BMT Hidayah Ummat. This study was conducted to determine the influence of sharia, services, products, and promotions on the demand of financing mudharabah at BMT Hidayah Ummah. Type of research is a field research with documentation of data collecting methods, because the data in this study is a secondary data. Where as this data obtained from customers data is filled directly. Analysis tool of this research is multiple linear regression tests that use the classicallinear regression tests and statistical tests. The resultof t-test analysis shows that each of the independent variables significantly affects the demand of financing in BMT Hidayah Umat Yogyakarta. In the F test shows that the sharia independent variables influences significantly, while theservice, product, and promotionare not influencing significantly for the demand of financing mudharabah. The determinants coefficient (R²) of 0.729, which means that the demand for financing mudharabah in BMT Hidayah Umat can be explained by the independent variables was 72.9%. The remaining of 27.1% is influenced by other variables out side this research. Keyword: Financing Mudharabah, BMT.